Best Answer

The question is incomplete in the sense that there is no +/- sign between q2 and 2q.

Considering plus '+' sign.

q3 - q2 + 2q - 2

q2(q - 1) + 2(q - 1)

(q2 + 2)(q - 1)

Considering minus '-' sign.

q3 - q2 - 2q - 2

The expression can't be factored.

However if we consider the question complete then it is written as:

q3 - q2(2q) - 2

q3 - 2q3 - 2

-q3 - 2

-(q + 21/3)(q2 - 21/3 + 22/3)

Q: What are the factors of q 3-q 2 2q-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

No. √18 cannot be expressed as a fraction of the form p/q. 18 = 2 x 9 = 2 x 32 ⇒ √18 = √(2 x 32) = (√2) x 3. So if √2 is rational then √18 is rational. Assume √2 is rational. Then p and q can be found such that √2 = p/q is in its simplest form, that is p and q have no common factor. Consider: (√2)2 = (p/q)2 ⇒ 2 = p2/q2 ⇒ p2 = 2q2 Thus p2 is even, and so p must be even. Let p = 2r. Then: p2 = (2r)2 = 2q2 ⇒ 4r2 = 2q2 ⇒ 2r2 = q2 Thus q2 is even, and so q must be even. Let q = 2s. Thus p = 2r, q = 2s and so p and q have a common factor of 2. But p and q are such that they have no common factor. Contradiction. Thus the assumption that √2 is rational is false, that is √2 is not rational, so √18 is not rational.

There are infinitely many such numbers.If p is a prime then p^11 has 12 factors.If p and q are any two primes, then p*q^5 has 12 factors.If p and q are any two primes, then p^2*q^3 has 12 factors.If p, q and r are any three primes, then p*q*r^2 has 12 factors.

If p = 50 of q then q is 2% of p.

If you mean, (by rational form), in the form "p/q", let p= -2 and q = 1

Consider have x^(p/q) where the base, x, is a whole number. p and q are also whole numbers (q is not 0) so that the exponent, p/q, is a fraction. Then x^(p/q) = (x^p)^(1/q), that is, the qth root of x^p or equivalently, x^(p/q) = [x^(1/q)]^p, that is, the pth power of the qth root of x. For example, 64^(2/3) = 3rd root of 64^2 = 3rd [cube] root of 4096 = 16 or (cube root of 64)^2 = 4^2 = 16. If p/q is negative, the answer is the reciprocal of the answer obtained with positive p/q.

Related questions

In its general form it works out as: 3px+qy-12p2-2q2 = 0Improved Answer:-Points:(p, q) and (7p, 3q)Slope: q/3pPerpendicular slope: -3p/qMidpoint: (4p, 2q)Equation: y-2q = -3p/q(x-4p) => yq = -3px+12p2+2q2Perpendicular bisector equation in its general form: 3px+qy-12x2-2q2 = 0

steps to solve 4(3q-q): =(4)(3q+-q) =(4)(3q)+(4)(-q) =12q-4 answer: 8q

First find the mid-point of the line segment which will be the point of intersection of the perpendicular bisector. Then find the slope or gradient of the line segment whose negative reciprocal will be the perpendicular bisector's slope or gradient. Then use y -y1 = m(x -x1) to find the equation of the perpendicular bisector. Mid-point: (7p+p)/2 and (3q+q)/2 = (4p, 2q) Slope or gradient: 3q-q/7p-p = 2q/6p = q/3p Slope of perpendicular bisector: -3p/q Equation: y -2q = -3p/q(x -4p) y = -3px/q+12p2/q+2q Multiply all terms by q to eliminate the fractions: qy = -3px+12p2+2q2 Which can be expressed in the form of: 3px+qy-12p2-2q2 = 0

First find the midpoint the slope and the perpendicular slope of the points of (p, q) and (7p, 3q) Midpoint = (7p+p)/2 and (3q+q)/2 = (4p, 2q) Slope = (3q-q)/(7p-p) = 2q/6p = q/3p Slope of the perpendicular is the negative reciprocal of q/3p which is -3p/q From the above information form an equation for the perpendicular bisector using the straight line formula of y-y1 = m(x-x1) y-2q = -3p/q(x-4p) y-2q = -3px/q+12p2/q y = -3px/q+12p2/q+2q Multiply all terms by q and the perpendicular bisector equation can then be expressed in the form of:- 3px+qy-12p2-2q2 = 0

3q = 18 q = 6

3q + 2z, although it could be 2*(3q+z)

If -3q + 4 = 13 then 3q = -9 : q = -3 If 6q = 13 then q = 13/6 = 2 1/6 The question contains an anomaly and is invalid.

30q3 + 14q2 - 4q = 0 can be factored as q(30q2 + 14q - 4) = 0 The bracketed term can be factored (30q2 + 14q - 4) = (10q - 2)(3q + 2) The equation can now be written : q(10q - 2)(3q + 2) = 0 The equation = 0 when either q = 0 or one of the bracketed terms = 0 When 10q - 2 = 0 then q = 2/10 = 1/5 : and when 3q + 2 = 0 then q = -2/3.

(3)(q-11) = 3q-33

2q + 21.

No. √18 cannot be expressed as a fraction of the form p/q. 18 = 2 x 9 = 2 x 32 ⇒ √18 = √(2 x 32) = (√2) x 3. So if √2 is rational then √18 is rational. Assume √2 is rational. Then p and q can be found such that √2 = p/q is in its simplest form, that is p and q have no common factor. Consider: (√2)2 = (p/q)2 ⇒ 2 = p2/q2 ⇒ p2 = 2q2 Thus p2 is even, and so p must be even. Let p = 2r. Then: p2 = (2r)2 = 2q2 ⇒ 4r2 = 2q2 ⇒ 2r2 = q2 Thus q2 is even, and so q must be even. Let q = 2s. Thus p = 2r, q = 2s and so p and q have a common factor of 2. But p and q are such that they have no common factor. Contradiction. Thus the assumption that √2 is rational is false, that is √2 is not rational, so √18 is not rational.

Factoring the left and right parts separately gives: q3 - q2 + 2q - 2 = q(q2 - 1) + 2(q - 1) = q(q + 1)(q - 1) + 2(q - 1) Now we have a common factor (q - 1) that we can take out. I'll combine the remaining terms again: (q - 1)[q(q + 1) + 2(q - 1)] = (q - 1)[q2 + q + 2q - 2] = (q - 1)(q2 + 3q - 2) The right part has no obvious factorization; but you can use the quadratic formula to get the factors, which will probably include square roots.